2018
DOI: 10.1155/2018/5712857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture at LR3 on Cerebral Glucose Metabolism in a Rat Model of Hypertension: A 18F‐FDG‐PET Study

Abstract: Our objective was to investigate the effect of acupuncture at LR3 on cerebral glucose metabolism in spontaneously hypertensive rats (SHRs). We used 18F-2-fluoro-deoxy-D-glucose positron emission tomography (18F-FDG-PET) to examine the effects of acupuncture at LR3 on cerebral glucose metabolism in SHRs. SHRs were randomly allocated to receive no treatment (SHR group), needling at LR3 (SHR + LR3 group), or sham needling (SHR + sham group). Rats received 10 min acupuncture once per day for 7 days and were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
11
0
2
Order By: Relevance
“…Consistent with previous studies, we selected LR3 and found that acupuncture significantly decreased the SBP, MBP, and HR in SHRs compared with WKYs, without any impact on normal BP. Moreover, some imaging studies showed that the effects of acupuncture on BP might involve altered cerebral or urinary metabolism [25, 26]. The molecular mechanism may be due to an increase in antioxidant enzyme in medulla according to a proteomic study [27].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we selected LR3 and found that acupuncture significantly decreased the SBP, MBP, and HR in SHRs compared with WKYs, without any impact on normal BP. Moreover, some imaging studies showed that the effects of acupuncture on BP might involve altered cerebral or urinary metabolism [25, 26]. The molecular mechanism may be due to an increase in antioxidant enzyme in medulla according to a proteomic study [27].…”
Section: Discussionmentioning
confidence: 99%
“…LR3 is in the Jueyin Liver Meridian of the Foot, a special acupuncture source point that has been used to relieve stress, headache, dizziness, and eyestrain. Stimulation of LR3 specifically activates areas in the brain [14], alters cerebral glucose metabolism in the hypothalamus [15], increases blood flow in the skin [16], and is used for treating peripheral circulatory failure in the foot, i.e., Raynaud's phenomenon [17,18]. According to Omole et al, stimulation of LI4 improves pain severity, joint stiffness, and the color of the fingers and toes [19].…”
Section: Discussionmentioning
confidence: 99%
“…A acupuntura não só diminuiu a PA, como também alterou metabolismo cerebral da glicose no hipotálamo, tálamo, medula oblonga e cerebelo. (28) Uma revisão de literatura concluiu que a acupuntura pode influenciar principalmente em fatores relacionados ao sistema nervoso, estresse oxidativo, sistema endócrino, função cardiovascular e fluxo sanguíneo em ratos hipertensos. Esses resultados podem indicar que a acupuntura é capaz de prevenir complicações por essas vias quando usada no tratamento da HAS.…”
Section: Discussionunclassified